2013
DOI: 10.1177/070674371305800405
|View full text |Cite
|
Sign up to set email alerts
|

The Costs Associated with Antidepressant Use in Depression and Anxiety in Community-Living Older Adults

Abstract: Objective: To determine the costs associated with antidepressant (AD) use by depression and anxiety status in a public-managed health care system. Methods:Data were obtained from a population-based health survey of 1869 older adults. Depression and anxiety were based on the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, criteria and measured at 2 time points 1 year apart. AD and health service use and costs were identified from provincial administrative databases and included hospitaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…In the elderly, antidepressant use is associated with increased risk of strokes, falls, fractures, hyponatraemia and death (Coupland et al, 2011). It also results in substantial healthcare costs (Health and Social Care Information Centre, 2017; Vasiliadis et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the elderly, antidepressant use is associated with increased risk of strokes, falls, fractures, hyponatraemia and death (Coupland et al, 2011). It also results in substantial healthcare costs (Health and Social Care Information Centre, 2017; Vasiliadis et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] This inappropriate use exposes patients to potentially serious adverse effects 9,10 and is costly. 11 Stopping antidepressants, however, is frequently associated with withdrawal symptoms, which can be problematic, and mistaken for relapse/ recurrence. 12 To minimize these symptoms, the American Psychiatric Association and the National Institute for Health and Care Excellence advise tapering doses over some weeks in most cases.…”
Section: Introductionmentioning
confidence: 99%
“…Canadian healthcare costs are generally lower than those in the US. Nonetheless, a recent population-based study from the province of Quebec found that overall healthcare costs were approximately $2,000 (CAD) higher for patients prescribed antidepressants, with a large proportion of increased costs attributed to patients without a recent history of depression or anxiety [54]. The cost of treatment, however, is only part of the cost of screening.…”
Section: Discussionmentioning
confidence: 99%